Marketing Strategies for Traditional Musical Instruments and Wood-based Souvenir - Samosir, Zurni Zahara; Lumbanraja, Prihatin; Sihotang, Ance Marintan; Siahaan, Elisabet (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Marketing is known as the most important element of any economic activity. Without a good marketing practices,, product will not be known to public. People will not purchase or consume products that they are completely unaware of. Siponjot Village, which is fostered as an art village, must be able to market its art so that they are widely recognized and recognized by the community. This community service program from the marketing side of village art products targets the creation of creative economic transactions as well as marketing activities for art products of Siponjot Village craftsmen, be it musical instruments, art performances, or crafts made by the people of Siponjot Village. During this occasion, the implementation team has provided a designs that can be used as brands / labels for Siponjot’s products.